Practicing Disconnection in The Digital Age - Dremljuga, Ramona-Riin (AoIR Selected Papers of Internet Research, 2017)
This paper explores the management of connection through disconnecting practice, or more specifically, quitting some (social) media platforms while continuing to use other communication tools and information systems. By studying the lived experience of these individuals who, after having actively used the tool or platform, deliberately delete an account to distance themselves from the platform’s services or its other users, I argue that this action to disconnect does not equate to disconnectivity, but instead creates new structures for connectivity. This paper presents partial findings from a larger study of people who self-identify as disconnecting. The material to date has been gathered from semi-structured interviews with twelve participants, continuing to interview people from a range of demographics. This demonstrates a theoretical sampling (c.f., Charmaz, 2006), since the focus is to explore a particular type of disconnection, regardless of participant demographic. The preliminary analysis adds depth to what previous literature tells us about the experience of disconnecting which is often perceived as a negative response to technology, or a desire to escape. Below the surface of popular media explanations, we find that these practitioners of disconnection are making reasoned decisions about how they want to experience digital culture, not necessarily escape from it. As they are pushed to find alternatives for technology-supported connection that fit better with their needs and personal preferences, the disconnected find workarounds or learn to settle with less. Consequently, while denying a system, a new structure for staying connected is created based on other available tools.